2006
DOI: 10.1159/000102050
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Thrombin Potential for Predicting Risk of Venous Thromboembolism in Carriers of Factor V Leiden

Abstract: Measurement of endogenous thrombin potential (ETP) detects hypercoagulability and can be used to identify activated protein C resistance due to factor V Leiden (FVL). However, not all carriers of FVL suffer thrombosis and therefore we sought to determine if the test for ETP could be modified in such a way as to enable detection of FVL patients who were at increased risk of venous thromboembolism. Protac, an activator of both protein C and factor V, was incorporated into the traditional thrombin generation reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 37 publications
3
18
0
Order By: Relevance
“…Such a finding could be a part of the explanation behind the differences in the phenotypes of patients with FV Leiden, i.e. that most of them do not experience any thromboembolic episodes whereas others suffer recurrent thrombotic episodes [77].…”
Section: Aimmentioning
confidence: 97%
See 2 more Smart Citations
“…Such a finding could be a part of the explanation behind the differences in the phenotypes of patients with FV Leiden, i.e. that most of them do not experience any thromboembolic episodes whereas others suffer recurrent thrombotic episodes [77].…”
Section: Aimmentioning
confidence: 97%
“…The authors showed that the ETP ratio [ETP measured in the presence of Protac ® ]/ [ETP measured in the absence of Protac ® ] was significantly higher in FV Leiden heterozygotes than in controls. Within the FV Leiden group, patients with a history of thrombosis had higher, but statistically not significant, ETP ratios compared with those without [77]. Hron et al, however, refuted the notion that thrombin generation is enhanced in individuals who are carriers of the FV Leiden mutation.…”
Section: Thrombin Generation In Patients With Factor V Leiden and Thementioning
confidence: 98%
See 1 more Smart Citation
“…Although some plasma factors such as levels of TF pathway inhibitor or levels of factor II and increased endogenous thrombin potential are linked to the thrombotic risk in subjects with FV Leiden and PT20210A, no definite risk stratification strategy using laboratory testing has yet been proven to be clinically useful in predicting thrombosis in carriers [62][63][64]. The inference that circulating MPs may contribute to the thrombogenic profile of FV Leiden carriers were drawn from the following observations: first, there is an approximately 10-to 20-fold reduction in the rate of activated protein C (APC) catalyzed inactivation of plasma-derived factor Va when bound to synthetic phospholipid vesicles [65]; second, APC can induce endothelial MPs production and APC bound to endothelial MPs is no longer capable of FVa inactivation [66].…”
Section: Mps and Hereditary Thrombophiliamentioning
confidence: 99%
“…It is, however, not standardized; it is influenced by many preanalytical variables and there is a high inter-laboratory variability due to different reagents and their concentrations, making it difficult to establish reference ranges (Castoldi & Rosing 2011). Thrombin generation is elevated in antithrombin deficiency (Wielders et al, 1997;AlhencGelas et al, 2010), protein S deficiency (Castoldi et al, 2010), protein C deficiency (Hezard et al, 2007), in carriers of factor V Leiden (Hezard et al, 2006;Lincz et al, 2006) and prothrombin G202010 mutation (Kyrle et al, 1998;Lavigne-Lissalde et al, 2010). It is also associated with the presence of antiphospholipid antibodies (Liestol et al, 2007;Devreese et al, 2009) and increased levels of factors VIII (ten Cate-Hoek et al, 2008), IX and XI (Siegemund et al, 2004).…”
Section: Global Haemostasis Screening Assaysmentioning
confidence: 99%